FEATURES OF METABOLIC SYNDROME IN WOMEN OF EARLY REPRODUCTIVE AGE WITH POLYCYSTIC ОVARY SYNDROME - ANZHELIKA Y. Beglova; SVETLANA I. Yelgina; ELENA V. Bryukhina; ELENA V. Rudaeva (Фундаментальная и клиническая медицина)
Aim. To determine the features of metabolic syndrome in women of early reproductive age with polycystic ovary syndrome. Materials and Methods. We recruited 60 consecutive women of early reproductive age, further dividing them into the groups with and without polycystic ovary syndrome (n = 30 per group). Metabolic syndrome was diagnosed by the National Cholesterol Education Program's Adult Treatment Panel III (NCEP ATP III) criteria. Results. Metabolic syndrome was diagnosed in 22 (73.3%) women of early reproductive age with and in 8 women (26.4%) without polycystic ovary syndrome (p = 0.0001). Expectedly, all criteria for the diagnosis of metabolic syndrome were more SHAPE \* MERGEFORMAT English frequently detected in women with polycystic ovary syndrome compared to those without: obesity (p = 0.005), waist-hip circumference ratio > 0.85 (p = 0.049), blood pressure > 140/90 mmHg (p = 0.028), high level of triglycerides (p = 0.0001) and fasting plasma glucose (p = 0.0001) and low level of high-density lipoprotein cholesterol (p = 0.0001). Conclusions. Women of early reproductive age with polycystic ovary syndrome have higher prevalence of metabolic syndrome and its diagnostic criteria as compared to those without.